The Role of Magnetic Resonance Imaging in Preoperative Planning for Patients Undergoing Therapeutic Mammoplasty. (17th December 2013) - Hicks, Gareth; Turton, Philip; Rajan, Sree; Nunn, April; Sharma, Nisha; Achuthan, Raj
Abstract : Background . Assessment of the ratio between tumour volume and breast volume in therapeutic mammoplasty is paramount. Traditionally based on clinical assessment and conventional breast imaging, the role of breast magnetic resonance imaging (MRI) in this context has not been established. Methods . Data was collected from all women undergoing therapeutic mammoplasty (TM) between 2006 and 2011. Each case was discussed at an MDT where MRI was considered to facilitate surgical planning. The contribution of MRI to disease assessment and surgical outcome was then reviewed. Results . 35 women underwent TM, 15 of whom had additional MRI. 33% of patients within the MRI subgroup had abnormalities not seen on either mammography or USS. Of those undergoing MRI, 1/15 patients required completion mastectomy versus 3 patients requiring completion mastectomy and 1 patient requiring further wide local excision (4/20) in the conventional imaging group. No statistical difference was seen between size on MRI and size on mammography versus final histological size, but a general trend for greater correlation between size on MRI and final histological size was seen. Conclusion . MRI should be considered in selected patients undergoing therapeutic mammoplasty. Careful planning can identify those who are most likely to benefit from MRI, potentially reducing the need for further surgery.